Radical Nationalists in Austria and Switzerland: Cooperation in the Authorities - Gribovsky Vasily (Научно-аналитический вестник Института Европы РАН, 2018)
Due to the acute migration crisis in Europe, the issue of immigration and a number of related topics are on the agenda of protest parties. It is about interethnic relations and Islamism, the growth of crime and terrorist threat, as well as the growing burden on social systems. Nowadays the prosperous countries of the Alpine region face these challenges – not only Austria, but also Switzerland, which is not part of the European Union, but no less attractive to immigrants and refugees